Exploring the Synergistic Effect of Novel Ni‐Fe in 2D Bimetallic Metal‐Organic Frameworks for Enhanced Electrochemical Reduction of CO2. Issue 1 (28th November 2021) - Iqbal, Rashid; Akbar, Muhammad Bilal; Ahmad, Aziz; Hussain, Arshad; Altaf, Naveed; Ibraheem, Shumaila; Yasin, Ghulam; Khan, Muhammad Abubaker; Tabish, Mohammad; Kumar, Anuj; Majeed, Muhammad K.; Saleem, Adil; et al.
Abstract: The two‐dimensional (2D) metal‐organic frameworks (MOFs) have capabilities to reduce CO2 with high Faradaic efficiency (FE). Herein, the role of incorporating bimetallic Ni and Fe into newly constructed MOFs is studied. This work highlights the use of bimetallic synergistic effect with surrounded nitrogen atoms, opening new avenues for efficient electrocatalytic reduction of CO2 . This MOF Ni‐Fe contains moieties surrounded by four nitrogen atoms via covalent bonding, which resembles the porphyrin‐based molecular units as selective and effective homogeneous CO2 reduction electrocatalysts. Besides, density functional theory (DFT) also helps to figure out that the incorporation combination of metals helps achieve the high FE of 98.2% with stability up to 30 h under a low applied potential of −0.5 V versus reversible hydrogen electrode (RHE). These results offer a promising avenue to develop and optimize the MOFs‐based electrocatalysts for electrochemical conversion of CO2 . Abstract : This work highlights the use of bimetals (Ni and Fe) into newly constructed metal‐organic frameworks (MOFs) and gives synergistic effect with surrounded nitrogen atoms that opens up new avenues for efficient electrocatalytic reduction of CO2 . Density functional theory (DFT) helps to understand that bimetallic MOF delivers the high Faradaic efficiency (FE) of 98.2% with stability up to 30 h at −0.5 V potential.